Correlations between Expenditure and Employees in R&D Activity by Performance Sectors from Romania - Vasilica Ciucă; Daniela Pașnicu; Gabriela Tudose; Mihai Robert Paşnicu (Revista Română de Statistică, 2016)
In the context of increased competition in the recent years, the innovation has become a key factor in economic development through better use of opportunities, capturing new markets and creating high quality jobs. A crucial element for achieving innovation is the R & D, due to the stock of knowledge created at the human, cultural and societal level and its use in designing new applications. In order to manage the funds better in R & D, stimulate competitiveness and attract new funds into R & D, given the target of Europe 2020 Agenda, the paper analyzes the correlation between expenditure and employees in R & D by performance sectors from Romania, and presents a mathematical model which might explain the dynamic of the structure of employees in business sector from R&D. It also considers the impact of the results on the capacity for innovation, economic development and future directions of action to increase investment in R & D, efficient use of intellectual capital and economic specialization.